GIS-Based Spatial Analysis of Groundwater Infiltration Potential in the Batang Pelangai Watershed - Arif Rahman Putra; Bigharta Bekti Susetyo; Yastika Sari; Dina Nanda Lestari; Ade Irwan; Alviqri Febriano; Andini Dolok Saribu; Reza Inka Febriani (Jambura Geoscience Review, 2026)
The Batang Pelangai watershed plays an important hydrological role in supporting groundwater recharge and regulating surface runoff in the coastal area of West Sumatra. However, land cover changes, topographic variation, and increasing land-use pressure have reduced the capacity of the watershed to absorb water. This study aimed to assess groundwater infiltration potential using a geographic information system-based weighted overlay approach. Four biophysical parameters–soil type, rainfall, land use, and slope gradient–were integrated through scoring, weighting, reclassification, and spatial overlay analysis. The results show that groundwater infiltration potential in the study area is dominated by the somewhat critical category, covering 27,861.04 ha or 49.53% of the total watershed area. The beginning critical category covers 16,488.41 ha or 29.31%, while the very critical category covers 11,452.27 ha or 20.37%. In contrast, areas classified as good and natural normal conditions are very limited, covering only 116.25 ha or 0.21% and 326.03 ha or 0.58%, respectively. These findings indicate that most of the Batang Pelangai watershed has low groundwater infiltration capacity due to the combined influence of slope, soil characteristics, rainfall distribution, and land-use conditions. The resulting infiltration potential map provides spatial information for prioritizing watershed conservation, land rehabilitation, infiltration enhancement, and sustainable water resource management in coastal watershed areas.